2018
DOI: 10.4081/reumatismo.2018.1011
|View full text |Cite
|
Sign up to set email alerts
|

The use of rituximab in idiopathic inflammatory myopathies: description of a monocentric cohort and review of the literature

Abstract: Rituximab (RTX), a chimeric monoclonal antibody targeted against CD20, has been used to treat refractory inflammatory myopathies (IIM). The primary objective of this study was to retrospectively assess the efficacy of RTX in reducing disease activity in patients with IIM refractory to conventional therapy. Secondary aim was the evaluation of adverse events (AE) during the treatment period. We examined 26 patients with a diagnosis of IIM, referred to our Rheumatology Unit and treated with RTX for active refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
3
1
1
Order By: Relevance
“…There were 2 patients who received RTX due to acute aggravation of organizing pneumonia, with normal serum CPK level (64 unit/dL and 79 unit/dL, respectively) and high ESR (116 mm/hr and 64 mm/hr, respectively). Unlike previous studies 42 43 which reported especially favorable responses to pulmonary involvement, the 2 patients mentioned above with organizing pneumonia did not fully recover after RTX treatment, and they did not achieve CPK reduction nor by their physician's opinion. Contrarily, one patient with generalized and refractory skin lesions with normal serum CPK (32 unit/dL), CRP (0.15 mg/dL) and ESR levels (18 mm/hr) had almost fully recovered after RTX treatment and was classified as a responder.…”
Section: Discussioncontrasting
confidence: 84%
“…There were 2 patients who received RTX due to acute aggravation of organizing pneumonia, with normal serum CPK level (64 unit/dL and 79 unit/dL, respectively) and high ESR (116 mm/hr and 64 mm/hr, respectively). Unlike previous studies 42 43 which reported especially favorable responses to pulmonary involvement, the 2 patients mentioned above with organizing pneumonia did not fully recover after RTX treatment, and they did not achieve CPK reduction nor by their physician's opinion. Contrarily, one patient with generalized and refractory skin lesions with normal serum CPK (32 unit/dL), CRP (0.15 mg/dL) and ESR levels (18 mm/hr) had almost fully recovered after RTX treatment and was classified as a responder.…”
Section: Discussioncontrasting
confidence: 84%
“…Although such a strategy has not been evaluated by randomised trials, several case reports and case series suggest that rituximab is an effective therapy for anti-SRP autoantibody associated IMNM, while IVIG has been quite successful in treating anti-HMGCR IMNM 16 17. This highlights the importance of serology in diagnosing patients with inflammatory myositis 15 18…”
Section: Discussionmentioning
confidence: 99%
“…99,100,102 Skin manifestations of patients with dermato-polymyositis would be sensitive to RTX only in some cases or not at all. [103][104][105][106] Dysphagia essentially proves unresponsive to RTX. 107 In short, off-label RTX therapy can be useful in several patients affected by refractory myositis.…”
Section: Idiopathic Inflammatory Myopathiesmentioning
confidence: 99%